Pengembangan Buku Referensi Etnobotani Cendana (Santalum album L.) Masyarakat Lokal Kabupaten Timor Tengah Selatan - Saridewi, Maria Paulin (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
Abstract The presence of sandalwood in the villages of Eonbesi and Oelbubuk is relatively good, but the local community only knows the use of sandalwood is limited to medical purposes. The sustainability of sandalwood requires the support of all parties and a means of education in the form of a reference book is needed to increase knowledge about sandalwood ethnobotany. The purpose of this development research is to raise awareness of the general public and students as an academic community group to be able to utilize, maintain, and process sandalwood, and produce products in the form of reference books. This study uses a development model adapted from Borg and Gall (2003) consisting of 5 stages. The subjects of this study were fourth semester students, Biology Education Study Program, Nusa Cendana University who were taking the High Botanical Botany course. The results of this study indicate that the ethnobotany reference book for sandalwood in the local community of Timor Tengah Selatan (TTS) district is feasible to be developed. The results of the assessment of high plant botanist validators (BTT), sandalwood experts, and experts in learning media were 80%, 75%, and 75% respectively which were valid.